Association between a history of depression and anti-müllerian hormone among late-reproductive aged women: the Harvard study of moods and cycles - Samuel W. Golenbock; Lauren A. Wise; Geralyn M. Lambert-Messerlian; Elizabeth E. Eklund; Bernard L. Harlow (BMC, 2020)
Abstract Background There is conflicting evidence regarding the association between a history of depression and risk of early menopause. In a cohort of premenopausal women, we investigated the association between depression history and ovarian reserve, as measured by anti-müllerian hormone (AMH). Methods The Harvard Study of Moods and Cycles (HSMC) was a prospective cohort study of women living in the Boston, MA metropolitan-area (1995-1999). Women aged 36-45 years at cohort entry (1995) were sampled from seven Boston metropolitan-area communities using census directories. We measured serum AMH in early-follicular phase venous blood specimens from 141 women with a Structured Clinical Interview for DSM-IV (SCID)-confirmed history of depression and 228 without such a history. We calculated prevalence ratios (PR) for the association between characteristics of depression history and low AMH (≤1.4 ng/mL), adjusting for several potential confounders. Results The prevalence of low AMH was similar among depressed (57.5%) and non-depressed (57.9%) women (Adjusted [Adj] PR = 0.90, 95% CI: 0.75, 1.08). Among depressed women, results were not appreciably different among those who had ever used antidepressants and those with comorbid anxiety. Modest inverse associations between depression and low AMH were seen among women aged 36-40 years (Adj PR = 0.75, 95% CI: 0.52, 1.09) and nulliparous women (Adj PR = 0.77, 95% CI: 0.59, 1.00). No dose-response association with greater duration or length of depressive symptoms was observed. Conclusions Overall, the prevalence of low AMH was similar for depressed and non-depressed women 36-45 years of age. Surprisingly, among younger and nulliparous women, those with a history of depression had a slightly reduced prevalence of low AMH relative to those without such a history. These results do not indicate reduced ovarian reserve among women with a history of depression.